Detection of DEL phenotype in RhD negative blood by freeze-thaw elution technique and sequence-specific prime polymerase chain reaction / Nordiana Nordin - Nordin, Nordiana (2015)
The weakest weak D called DEL phenotype was able to be detected via serological adsorption elution and molecular genotyping. In this study, the freeze-thaw elution and ssp-peR were used to detect the DEL phenotype. A total of 43 RhD negative samples collected from the National Blood Centre were serologically tested for Rh phenotyping and screened for DEL phenotype by both serological freeze-thaw elution and SSP-PCR. Based on the Rh phenotyping, the 43 RhD negative samples consisted of 34 ccee phenotype, 6 Ccee phenotype, 2 ccEe phenotype and 1 CCee phenotype. No DEL phenotype was detected by serological freeze-thaw elution but 2.33% (1/43) from the samples were detected for DEL phenotype that carried the RHD1227A allele by SSP-PCR. As a conclusion, the aim of this study was accomplished by the ability to detect DEL phenotype via molecular genotyping technique in distinguishing the DEL phenotype from truly D negative but not for freeze thaw elution technique.